2010
DOI: 10.1155/2010/786503
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Decay in Alcohol Abusers Compared to Alcohol and Drug Abusers

Abstract: Alcohol and drug abuse are detrimental to general and oral health. Though we know the effects of these harmful habits on oral mucosa, their independent and combined effect on the dental caries experience is unknown and worthy of investigation. We compared 363 “alcohol only” abusers to 300 “alcohol and drug” abusers to test the hypothesis that various components of their dental caries experience are significantly different due to plausible sociobiological explanations. After controlling for the potential confou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
2
24
1
10
Order By: Relevance
“…7 Drug, alcohol, and tobacco users have a higher incidence of oral conditions including oral candidiasis, periodontal problems, stomatitis and precancerous lesions. 8 In a study comparing “alcohol abusers only” to “alcohol and drug abusers,” Dasanayake et al 9 found that the alcohol and drug group had a 38% higher risk of having decayed teeth compared to the alcohol only group. Even among drug abusers with satisfactory oral hygiene, drug use has been associated with greater dental decay.…”
Section: Introductionmentioning
confidence: 99%
“…7 Drug, alcohol, and tobacco users have a higher incidence of oral conditions including oral candidiasis, periodontal problems, stomatitis and precancerous lesions. 8 In a study comparing “alcohol abusers only” to “alcohol and drug abusers,” Dasanayake et al 9 found that the alcohol and drug group had a 38% higher risk of having decayed teeth compared to the alcohol only group. Even among drug abusers with satisfactory oral hygiene, drug use has been associated with greater dental decay.…”
Section: Introductionmentioning
confidence: 99%
“…A study that evaluated the risk of caries among addicts who used only alcohol (n = 363) and those who use alcohol together with other drugs, especially marijuana, heroin and cocaine (n = 300), found that the group using alcohol and other drugs had 38% higher risk of having carious teeth compared to the group that consumed only alcohol (p<0.05) [23].…”
Section: Discussionmentioning
confidence: 99%
“…The high degree of polysubstance abuse in our sample makes it difficult to draw conclusions about the causative effects of methamphetamine use on oral health as alcohol, cocaine, and opiate use have all been associated with poor oral health (Abdollahi & Radfar, 2003;Brand, Gonggrijp, & Blanksma, 2008;Dasanayake et al, 2010;Rosenstein, 1975). Furthermore, more than half of our sample considered themselves homeless, which is a well-established predictor of increased oral health needs and low care utilization rates (Conte, Broder, Jenkins, Reed, & Janal, 2006;Gelberg, Linn, & Rosenberg, 1988;King & Gibson, 2003).…”
Section: Importance Of Primary Findingsmentioning
confidence: 94%